Quantitative analysis of the effect of end‐tidal carbon dioxide on regional cerebral oxygen saturation in patients undergoing carotid endarterectomy under general anaesthesia. (26th October 2017) - Ki, Seung‐Hee; Rhim, Jin‐Ho; Park, Jae‐Hong; Han, Young‐Jin; Cho, Yong‐Pil; Kwon, Tae‐Won; Choi, Byung‐Moon; Noh, Gyu‐Jeong
Abstract : Aims: Regional cerebral oxygen saturation (rSO2 ) is currently the most used measure in clinical practice to monitor cerebral ischaemia in patients undergoing carotid endarterectomy (CEA). Although end‐tidal carbon dioxide (PET CO2 ) is known as a factor that influences rSO2, the relationship between PET CO2 and rSO2 has not been quantitatively evaluated in patients with severe arteriosclerosis. This study aimed to evaluate the effect of PET CO2 on rSO2 in patients undergoing CEA under general anaesthesia. Methods: The intervention to change PET CO2 was conducted between skin incision and clamping of the carotid artery. The rSO2 values were observed by changing PET CO2 in the range of 25–45 mmHg. The PET CO2 –rSO2 relationship was characterized by population analysis using a turnover model. Results: In total, 1651 rSO2 data points from 30 patients were used to determine the pharmacodynamic characteristics. Hypertension (HTN) and systolic blood pressure (SBP) were significant covariates on the slope factor in the stimulatory effect of PET CO2 on rSO2 and fractional turnover rate constant ( kout ), respectively. The estimates of the parameters were kout (min −1 ): 3.59 for SBP <90 mmHg and 0.491 for SBP ≥90 mmHg, slope : 0.00321 for patients with HTN and 0.00664 for patients without HTN. Conclusion: The presence of HTNattenuates the response of rSO2 after a change in PET CO2 . When cerebral blood flow is in a state of decline caused by a decrease in SBP to <90 mmHg, the response of rSO2 to PET CO2 is increased. It is advisable to maintain SBP >90 mmHg in patients with HTNduring CEA.